Satisfaction with work life balance programs and its relationship with work related outcomes. [article]. - Cementina, Raquel S. .
As a response to the rapid changes in the work environment, organizations continue nto create programs that help employees attain work life balance. This study on call center employees explored the relationship of employee satisfaction with work-life balance programs on perceived job stress level and positively with organizational commitment. However, it failed to show a relationship between satisfaction with work life balance programs and turnover intent. Implications of the study were discussed.